To find the solution of the system of equations given by \( y = 4x - 10 \) and \( y = -2x + 8 \), we need to set the equations equal to each other:
\[ 4x - 10 = -2x + 8 \]
Now, let's solve for \( x \):
-
Add \( 2x \) to both sides: \[ 4x + 2x - 10 = 8 \] \[ 6x - 10 = 8 \]
-
Add \( 10 \) to both sides: \[ 6x = 18 \]
-
Divide by \( 6 \): \[ x = 3 \]
Now, substitute \( x = 3 \) back into one of the original equations to find \( y \). We'll use \( y = 4x - 10 \):
\[ y = 4(3) - 10 \] \[ y = 12 - 10 \] \[ y = 2 \]
Thus, the solution to the system of equations is:
\[ \boxed{(3, 2)} \]